Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

HCF of a and b = x

let the LCM = m

a = xy

let the LCM = m

a = xy

**So LCM is****bx.**### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

As we know H.C.F*L.C.M=product of two numbers
Therefore,
X* L.C.M=a*b
L.c.m=a b/x
=xyb/x
X and x gets cancel and we get l.c.m as by